Implementasi Kebijakan Persyaratan dan Tata Cara Penerbitan Sertifikat Kelayakan Pengolahan di Unit Pengolahan Ikan Palembang - Maulindawati, Maulindawati; Hakim, Arif Rahman; Zuber, Konar (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2023)
Accordance with the Regulation of the Minister of Maritime Affairs and Fisheries of the RI Number 17/Permen-KP/2019 concerning Requirements and Procedures for Issuing Processing Feasibility Certificates, Guidelines and procedures for good fish processing to ensure fishery products are safe and meet the requirements for quality assurance and safety of fishery products, methods Good fish processing is a guideline and procedure for good fish processing. Meanwhile, Sanitation Standard Operating Procedures are instructions and processes for implementing good sanitation to meet the needs for quality assurance and safety of fishery products. Fish Processing Industry Business Actors are required to follow Sanitation SOPs and implement good fish processing methods in each fish processing unit. The aim of this research is to determine the implementation of the Policy Requirements and Procedures for Issuing Processing Feasibility Certificates in Palembang Fish Processing Units. The problems in the research are the environment of the processing facilities and their control, the condition of the processing room building (lay out) of the processing kitchen which does not meet the specified standards, the low desire of the Fish Processing Unit/Business Actor in obtaining a Good Manufacturing Practices (GMP) permit for the reason that they are lazy in completing the requirements and the actors Businesses still have difficulty making improvements that comply with Good Manufacturing Practices (GMP)/ Sanitation Standard Operating Procedures (SSOP) standards due to cost/budget limitations. The data analysis technique used in this research is a qualitative data analysis technique. This research shows that: overall the implementation of the Policy on Requirements and Procedures for Issuing Processing Feasibility Certificates in the Palembang Fish Processing Unit has been implemented properly, although in its implementation there are still obstacles/constraints such as the environment of processing facilities and their control, the condition of the processing room building (lay out). ) processing kitchens do not meet the specified standards, low willingness of Fish Processing Units/business actors to obtain Good Manufacturing Practices (GMP) permits for reasons of being lazy in completing the requirements and business actors still have difficulty carrying out repairs that comply with Good Manufacturing Practices (GMP)/Sanitation standards Standard Operating Procedures (SSOP) due to cost/budget limitations